Case Report: Outcome of Osimertinib Treatment in Lung Adenocarcinoma Patients With Acquired KRAS Mutations - Xiu, Weigang; Zhang, Qianqian; Yu, Min; Huang, Yin; Huang, Meijuan (Frontiers in Oncology, 2021)
Background: Osimertinib belongs to the third-generation epidermal growth factor receptor tyrosine kinase inhibitor that has shown positive effects in treating lung adenocarcinoma cancer. However, the subsequent resistance to Osimertinib has become a clinical challenge. Case presentation: We present two lung adenocarcinoma cases that developed a resistance to Osimertinib. Among them, one patient attained both KRAS exon 2 and exon 3 mutations and was given paclitaxel (albumin-bound) plus carboplatin. The other patient exhibited a KRAS exon 3 mutation, so the paclitaxel (albumin-bound) plus nivolumab was administered. Eventually, the second patient manifested a better clinical outcome than the first. Conclusion: These results provide supporting evidence that KRAS exon 3 (R68S) mutations may be associated with Osimertinib resistance in lung adenocarcinoma patients. This further reveals the relationship between subtypes of acquired KRAS mutations and the effect of therapeutic approaches. Moreover, the combination of chemotherapy and immune checkpoint inhibitors may generate a satisfying disease control.